Innovations in the field of marketing as a factor for increasing the competitiveness of domestic dairy processing factories - Krykavskyi, Y. V.; Kosar, N. S.; Stets, О. М. (Видавництво Львівської політехніки, 2014)
The article studies the peculiarities of Ukrainian milk and dairy products market under current conditions. It substantiates steps to improve the competitiveness of milk processing factories by implementing innovations in their product marketing and sales policy. The effectiveness of such measures is proven in the context of a domestic milk processing company. Досліджено особливості ринку молока та молокопродуктів України у сучасних умовах. Обґрунтовано заходи щодо підвищення конкурентоспроможності продукції молокоперобних підприємств шляхом втілення інновацій у їх маркетингову товарну та збутову політику. Доведено ефективність використання таких заходів на прикладі вітчизняного молокоперобного підприємства.
Інновації у сфері маркетингу як фактор підвищення конкурентоспроможності вітчизняних молокопереробних підприємств
Keywords: product competitiveness; milk and dairy products market; marketing innovations; product quality; producer’s marketing departments; конкурентоспроможність товару; ринок молока та молокопродуктів; інновації у сфері маркетингу; якість продукції; власні збутові підрозділи виробника